2017
DOI: 10.15430/jcp.2017.22.4.248
|View full text |Cite
|
Sign up to set email alerts
|

TP53 R72P Polymorphism and Susceptibility to Human Papillomavirus Infection Among Women With Human Immunodeficiency Virus in Morocco: A Case-control Study

Abstract: BackgroundHuman papillomavirus (HPV) is the most common sexually transmitted agent worldwide. HPV is the main causative agent for cervical cancer. The HPV oncoprotein E6 binds to the tumor suppressor gene product p53, promoting its degradation; the Arg allele of TP53 R72P polymorphism binds more ardently with HPV E6 than the Pro variant. Here, we investigated whether TP53 R72P gene variant, rs104252, was associated with susceptibility to HPV infection in women with human immunodeficiency virus (HIV).MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…One of such genetic factors that increase susceptibility to HPV-associated cervical carcinogenesis is the TP53 R72P mutation ( 238 ), which was reported in Gabon, Senegal, Sudan, Morocco, and South Africa; and this risk increases when combined with the chromosomal allelic loss of RB or with aberrant methylation of DAPK1 , RARB , TWIST1 , and CDH13 ( 79 , 239 244 ). Furthermore, aberrant methylation of these genes was proposed by Feng et al ( 245 ) to be useful in Senegal for the screening of cervical cancer, either alone or in combination with cytology.…”
Section: Resultsmentioning
confidence: 99%
“…One of such genetic factors that increase susceptibility to HPV-associated cervical carcinogenesis is the TP53 R72P mutation ( 238 ), which was reported in Gabon, Senegal, Sudan, Morocco, and South Africa; and this risk increases when combined with the chromosomal allelic loss of RB or with aberrant methylation of DAPK1 , RARB , TWIST1 , and CDH13 ( 79 , 239 244 ). Furthermore, aberrant methylation of these genes was proposed by Feng et al ( 245 ) to be useful in Senegal for the screening of cervical cancer, either alone or in combination with cytology.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies examined the relation between p53 gene polymorphism and the susceptibility to disease but the results of these studies are Contradictory, P53 polymorphism associated with the HPV infection and development of head and neck cancers 3 , development of oral cancer 14 and cervical cancer 19 , In contrast, some studies found the opposite result where the P53 gene poly-morphism are not associated with HPV infections ans lesion progressions 1 and development of skin cancer 20 .…”
Section: Discussionmentioning
confidence: 99%
“…P53 are tumor suppressor proteins which play an important role in regulation of cell cycles, maintenance of genomic integrities, and encounter of environmental insults and cell apoptosis in addition to controlling the innate immunity of viral infection by regulate several sensors and receptors 1 . These proteins are encoded by P53 genes which located in human chromosome 17 , a common single nucleotide polymorphism (SNP) located in this gene in codon 72 is the changing of CCC coding for Proline to CGC coding for Arginine, this polymorphism found in P53 region rich with Proline 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study was performed in 236 consecutive patients followed (or treated) at the Infectious Disease Center, University Hospital Center, Ibn Rochd (Casablanca, Morocco) from February 2013 to September 2018 as described previously [32,33]. All of the participants provided informed written consent as per the study protocol approved by the Ethics Committee of the Faculty of Medicine of Casablanca.…”
Section: Study Populationmentioning
confidence: 99%